Analysis of the Variation of the Oxygen Isotopic Composition of Mammalian Bone Phosphate - Stuart-Williams, Le Quesne Hilary (My University, 1996)
For the oxygen isotopic composition of bone and other biogenic phosphates to be a useful palaecclimatic tool it is necessary to process large numbers of samples precisely and rapidly. This study describes the development of robust and rapid analytical methods to achieve this and demonstrates their use in two practical studies.
Silver orthophosphate was chosen as the most suitable compound for oxygen isotopic analysis of phosphates due to its defined stoichiometry and lack of structural or adsorbed water. Biogenic phosphates are processed to silver phosphate by dissolution in acetic acid, followed by removal of the calcium as calcium oxalate and sequestering of the phosphate as lead phosphate. Organic material is then oxidized by heating with concentrated nitric acid and hydrogen peroxide before lead phosphate is reprecipitated and the lead removed as lead sulphate, leaving the phosphate in solution. The phosphate is precipitated as coarse crystals of silver orthophosphate by evaporation of an ammoniacal silver nitrate solution.
Oxygen is liberated from the silver orthophosphate by polymerization and reaction with bromine gas at 550°C in a vacuum line. Bromine is a catalyst and a reactant in the process; electrons are transferred from the oxygen to the bromine to catalyze the reaction and the silver is stabilised as silver bromide to prevent back-reaction. The isotopic composition of the gaseous oxygen is determined only by the temperature of the reaction and the isotopic composition of the silver orthophosphate. The product polymer consists of three to four phosphate ions, so that the reaction yields rather less than one oxygen atom from each phosphate ion or about 17% of the total oxygen.
Sixteen beaver (Castor canadensis) were obtained from October through May in southern Ontario. Enamel was ground from their continuously growing incisors, and a smaIl sample of bone was removed from each of their mandibles. The phosphate was analyzed using the methods described above. The results showed a seasonal variation in the δ¹⁸O of their incisor enamel of approximately 4‰. The δ¹⁸O of the beaver's body water decreases gradually through the winter and spring, rising rapidly in the summer. Seasonal fluctuation was not reflected in the δ¹⁸O of the adult beaver bone which was almost constant over the whole area. A Sangamonian giant beaver (Castoroides ohioensis) incisor obtained from Hopwood Farm, Illinois gave a climatic response curve similar to the Castor samples but the tooth grew more slowly and recorded 1.3 years of growth, with seasonal fluctuation in δ¹⁸O of 5‰ and a mean value about 5‰ heavier than in the modern beaver studied, reflecting a warmer climate with significant annual temperature fluctuation.
The city of Teotihuacan, near modern Mexico City, expanded in size rapidly from 100 BC to 200 AD due to substantial immigration from areas including the Gulf and Pacific seaboards where the δ¹⁸O of rain is substantially different from rain at Teotihuacan. Individuals who died before their bones could completely remodel should preserve this different signature in the δ¹⁸O of their bones. Samples (mostly ribs) from sixty-four individuals were analyzed, representing the major ethnic barrios in the city, the mass sacrifices associated with the foundation of the Temple of Quetzalcoatl and inhabitants of the Valley of Oaxaca: the supposed homeland of some of the immigrants. The δ¹⁸O of the bones had apparently not altered, despite diagenetic effects which were identified by infrared spectra, x-ray diffraction and elemental analyses. Distinct differences in δ¹⁸O were found between different groups in the city but these were not clearly related to their ethnic origins. The samples from the hotter and lower Valley of Oaxaca were analyzed and found to have lower δ¹⁸O than the inhabitants of Teotihuacan, the opposite of the expected relationship. This reversal was ascribed to Oaxaca being in lite rain shadow of the mountains.
Keywords: Geology; Geology